2010
DOI: 10.1094/phyto-100-1-0091
|View full text |Cite
|
Sign up to set email alerts
|

Involvement of the Plant Polymer Suberin and the Disaccharide Cellobiose in Triggering Thaxtomin A Biosynthesis, a Phytotoxin Produced by the Pathogenic Agent Streptomyces scabies

Abstract: Streptomyces scabies is a gram-positive soil bacterium recognized as the main causal agent of common scab. Pathogenicity in Streptomyces spp. depends on their capacity to synthesize phytotoxins called thaxtomins. Genes involved in biosynthesis of these secondary metabolites are known to be induced by cellobiose, a plant disaccharide. However, growth of S. scabies in a minimal medium containing cellobiose as a carbon source is very poor and only generates traces of thaxtomins. The effect of suberin, a lipid pla… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
31
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 37 publications
(39 citation statements)
references
References 29 publications
3
31
0
Order By: Relevance
“…Leiminger et al (2012) and Wanner (2009) also isolated pathogenic but txtAB-negative S. acidiscabies, S. stelliscabiei and S. bottropensis from Germany and North America respectively. Lerat et al (2010) pointed out that pathogenicity depends on the ability of the species to synthesize toxins. Little is known about the molecular mechanisms involved in Streptomyces pathogenicity.…”
Section: Discussionmentioning
confidence: 99%
“…Leiminger et al (2012) and Wanner (2009) also isolated pathogenic but txtAB-negative S. acidiscabies, S. stelliscabiei and S. bottropensis from Germany and North America respectively. Lerat et al (2010) pointed out that pathogenicity depends on the ability of the species to synthesize toxins. Little is known about the molecular mechanisms involved in Streptomyces pathogenicity.…”
Section: Discussionmentioning
confidence: 99%
“…Morphology of the five Streptomyces species tested in this study was determined as previously described (19). Briefly, 30–50 viable spores from each species were streaked on Petri dishes containing solidified (15 g L −1 agar) CM and SM.…”
Section: Methodsmentioning
confidence: 99%
“…It was revealed that its presence up-regulated proteins related to the stress response, glycolysis, morphological differentiation and secondary metabolism (17). The effect of suberin on differentiation was corroborated by cultivating S. scabiei in the presence or absence of suberin (19). Suberin strongly stimulates aerial mycelium development in S. scabiei which, in the presence of cellobiose, can lead to the production of the secondary metabolites, thaxtomins (19).…”
mentioning
confidence: 89%
See 1 more Smart Citation
“…Requirements of plant extracts such as oatmeal for thaxtomin production by S. scabies have been reported (Beauséjour et al 1999), and effective ingredients were shown to be suberin and cellobiose (Beauséjour et al 1999;Johnson et al 2007;Lerat et al 2010). We examined the requirements for phytotoxin production in S. turgidiscabies strain 65 and NBRC16080…”
Section: Effect Of Plant Extracts On Phytotoxin Productionmentioning
confidence: 99%